Strategi Penerapan Digital Marketing Berbasis Media Sosial Dalam Meningkatkan Volume Minat Konsumen Di LPLG BNKP (Jurnal Ilmu Sosial Dan Politik, 2025)
This research aims to analyze the strategy of implementing social media–based digital marketing in increasing consumer interest volume at LPLG BNKP. The study is motivated by a decline in customer visits over recent months and the suboptimal use of digital platforms as promotional media. In the digital era, social media plays a crucial role in building brand awareness, enhancing customer engagement, and influencing consumer decision-making. Therefore, this study seeks to understand how digital marketing strategies are applied and what factors influence consumer interest in LPLG BNKP’s products and services. The research employs a qualitative descriptive approach, using in-depth interviews, observation, and documentation as data collection techniques. Informants include the LPLG BNKP coordinator, employees, and consumers. Data were analyzed using the Miles & Huberman interactive model, consisting of data collection, data reduction, data display, and conclusion drawing.The findings show that LPLG BNKP has implemented several digital marketing strategies, including content marketing, social media marketing, influencer marketing, e-mail marketing, and video marketing. Content marketing is considered informative but still lacks detailed explanations regarding promotions and purchase procedures. Social media interactions help consumers, although response consistency needs improvement. Influencer marketing is effective for younger audiences but less influential for consumers who prioritize price and availability. E-mail marketing is not yet used optimally, whereas video marketing attracts consumers but requires shorter and more concise content for better engagement. The study also reveals that consumer interest is influenced by several factors: attention triggered by attractive content design, interest arising from relevant information and customer testimonials, desire driven by convenience and promotional offers, and satisfaction related to regularly updated information. However, delayed responses from social media administrators reduce consumer satisfaction and require further improvement.Overall, social media–based digital marketing has proven effective in increasing consumer awareness, interest, and intention toward LPLG BNKP’s products and services. Nonetheless, its implementation has not yet been fully optimized. Enhancing content quality, expanding platform usage, and improving digital service consistency are essential steps to maximize the positive impact of digital marketing on consumer interest.This research aims to analyze the strategy of implementing social media–based digital marketing in increasing consumer interest volume at LPLG BNKP. The study is motivated by a decline in customer visits over recent months and the suboptimal use of digital platforms as promotional media. In the digital era, social media plays a crucial role in building brand awareness, enhancing customer engagement, and influencing consumer decision-making. Therefore, this study seeks to understand how digital marketing strategies are applied and what factors influence consumer interest in LPLG BNKP’s products and services.The research employs a qualitative descriptive approach, using in-depth interviews, observation, and documentation as data collection techniques. Informants include the LPLG BNKP coordinator, employees, and consumers. Data were analyzed using the Miles & Huberman interactive model, consisting of data collection, data reduction, data display, and conclusion drawing.The findings show that LPLG BNKP has implemented several digital marketing strategies, including content marketing, social media marketing, influencer marketing, e-mail marketing, and video marketing. Content marketing is considered informative but still lacks detailed explanations regarding promotions and purchase procedures. Social media interactions help consumers, although response consistency needs improvement. Influencer marketing is effective for younger audiences but less influential for consumers who prioritize price and availability. E-mail marketing is not yet used optimally, whereas video marketing attracts consumers but requires shorter and more concise content for better engagement.The study also reveals that consumer interest is influenced by several factors: attention triggered by attractive content design, interest arising from relevant information and customer testimonials, desire driven by convenience and promotional offers, and satisfaction related to regularly updated information. However, delayed responses from social media administrators reduce consumer satisfaction and require further improvement.Overall, social media–based digital marketing has proven effective in increasing consumer awareness, interest, and intention toward LPLG BNKP’s products and services. Nonetheless, its implementation has not yet been fully optimized. Enhancing content quality, expanding platform usage, and improving digital service consistency are essential steps to maximize the positive impact of digital marketing on consumer interest.